In vitro antifilarial effects of three plant species against adult worms of subperiodic Brugia malayi - M.Z., Zaridah; Idid, S.Z.; Wan Omar, A.; S., Khozirah (Elsevier, 2001)
Five aqueous extracts from three plant species, i.e., dried husks (HX), dried seeds (SX) and dried leaves (LX) of Xylocarpus granatum (Meliaceae), dried stems (ST) of Tinospora crispa (Menispermaceae) and dried leaves (LA) of Andrographis paniculata (Acanthaceae) were tested in vitro against adult worms of subperiodic Brugia malayi. The relative movability (RM) value of the adult worms over the 24-h observation period was used as a measure of the antifilarial activity of the aqueous extracts. SX extract of X. granatum demonstrated the strongest activity, followed by the LA extract of A. paniculata, ST extract of T. crispa, HX extract and LX extract of X. granatum.